Effectiveness of Email Marketing in Improving Online Business Customer Retention - Novitasari, Angel; Agustina, Sri (Pusat Riset, Yayasan Cinta Negara Indonesia, 2025)
This study aims to analyze the effectiveness of using email marketing in improving customer retention in online businesses. Along with the rapid development of e-commerce in Indonesia, customer retention is a crucial factor for long-term success. This research uses a qualitative approach with in-depth interviews with online businesses and active customers who use e-commerce platforms in Indonesia. The data collected was analyzed using thematic analysis techniques to understand how email marketing plays a role in retaining customers and influencing their loyalty to online businesses. The results show that personalized email marketing that is relevant to customer needs can increase engagement and encourage repeat purchases, leading to increased customer retention rates. The research also found that frequency of email delivery and content tailored to customer preferences are important factors in the effectiveness of email marketing campaigns. However, some challenges such as over-delivery and lack of personalization were also identified, which could negatively impact customer retention. The practical implications of this research provide insights for online businesses to design email marketing strategies that are more effective in retaining their customers. This research also contributes to the development of theories related to the use of email marketing for customer retention in the Indonesian market, which is still limited in previous studies